LEXICAL AND GRAMMATICAL FEATURES OF KINSHIP TERMS IN AZERBAIJANI DIALECTS (Scientific journal of the Fergana State University, 2026)
Based on dialectological material collected from various dialects of the Azerbaijani language, this article analyzes the phonetic differences, morphological forms, and semantic nuances of kinship terms. Comparative data are presented on phonetic variants of words with identical meanings used in different regions, as well as unique kinship terms specific to certain localities. This approach provides valuable scientific insights into the richness of Azerbaijani dialects and their connection to the historical and cultural environment. Furthermore, the study explores the relationship between Turkic-origin kinship terms and the ancient layers of the language. The findings demonstrate that these terms reflect not only intra-family and societal relationships but also the spiritual values of the people, historical memory, and social structure.